Live Combined Bacillus subtilis and Enterococcus faecium Ameliorate Murine Experimental Colitis by Immunosuppression - S. Chen; Y. Fu; L. L. Liu; W. Gao; Y. L. Liu; S. H. Fei; Y. Tan; K. F. Zou (International Journal of Inflammation)
Live combined Bacillus subtilis and Enterococcus faecium ameliorate murine experimental colitis by immunosuppression manifested by downregulation of TLRs, macrophages, Th1, and Th2 but upregulation of Tregs.